Postdischarge outcomes of COVID-19 patients from South Asia: a prospective study. (28th April 2022) - Abeysuriya, Visula; Seneviratne, Suranjith L; De Silva, Arjuna P; Mowjood, Riaz; Mowjood, Shazli; de Silva, Thushara; de Mel, Primesh; de Mel, Chandima; Wijesinha, R S; Fernando, Amitha; de Mel, Sanjay; Chandrasena, Lal
Abstract: Background: Coronavirus disease 2019 (COVID-19) may cause clinical manifestations that last for weeks or months after hospital discharge. The manifestations are heterogeneous and vary in their frequency. Their multisystem nature requires a holistic approach to management. There are sparse data from the South Asian region on the outcomes of hospital-discharged COVID-19 patients. We assessed the posthospital discharge outcomes of a cohort of Sri Lankan COVID-19 patients and explored the factors that influenced these outcomes. Methods: Data were prospectively collected from patients who were discharged following an admission to the Nawaloka Hospital, Sri Lanka with COVID-19 from March to June 2021. At discharge, their demographic, clinical and laboratory findings were recorded. The patients were categorised as having mild, moderate and severe COVID-19, based on the Sri Lanka Ministry of Health COVID-19 guidelines. Following discharge, information on health status, complications and outcomes was collected through clinic visits and preplanned telephone interviews. A validated (in Sri Lanka) version of the Short Form 36 health survey questionnaire (SF-36) was used to assess multi-item dimensions health status of the patients at 1, 2 and 3 mo postdischarge. Results: We collected data on 203 patients (male, n=111 [54.7%]). The level of vaccination was significantly associated with disease severity (p<0.001). Early recovery was seen in the mild group compared with the moderate and severe groups. At 3 mo, on average 98% of mild and 90% of moderate/severe patients had recovered. Based on the SF-36, physical functioning dimensions, role limitation due to physical and emotional health, energy/ fatigue, emotional well-being, social functioning, pain and general health were significantly different in the moderate/severe vs mild COVID-19 groups at 1, 2 and 3 mo postdischarge (p<0.05). Twenty-three patients developed complications, of which the most common were myocardial infarction with heart failure (n=6/23; 26.1%), cerebrovascular accident (n=6/23; 26.1%) and respiratory tract infections (n=3/23; 13.01%) and there were six deaths. Conclusions: In our cohort, receiving two doses of the COVID-19 vaccine was associated with reduced disease severity. Those with mild disease recovered faster than those with moderate/severe disease. At 3 mo posthospital discharge, >90% had recovered.